Public Service Innovation Based on Digital Transformation as an Effort to Realize Smart Governance (International Journal of Social Welfare and Family Law, 2026)
This research investigates how digital transformation contributes to innovation in public services as part of the move toward smart governance. The study employs a literature review approach by evaluating a variety of pertinent materials, which include global journals, scholarly books, and official publications from the years 2018 to 2025. Results show that digital transformation notably enhances the quality of public services regarding their efficiency, effectiveness, openness, and ease of access. The incorporation of technologies like e-government platforms, mobile apps, artificial intelligence, and big data analysis allows governments to provide services that are quicker and more responsive. Additionally, digital platforms foster public involvement by offering means for communication and participation in decision-making activities. Despite these advancements, there are still several obstacles to overcome, such as the digital divide, insufficient infrastructure, low levels of digital skills, and resistance to change within bureaucracy. These issues emphasize the need for cohesive strategies that include investment in technology, development of human resources, and regulatory assistance. The study concludes that digital transformation is vital for achieving smart governance; however, its effectiveness relies on the preparedness of infrastructure, institutions, and society to embrace digital advancements.